Algebra 1

1: -(5)^-1
A: -1/5
B: -5
C: 5 *****
D: 1/5

2; (-4.7) ^0
A: 1***
B: -1
C: 0
D: -4.7

3:
-1/p^-6
A: -6/p-6
B: -6p ****
C: -p^6
D: p^6

4: 6^3 x 6^10
A: 36^13
B: 6^13
C: 6^30 *****
D: 18^30

Simplify this expression (-4) ^-6 (-4) ^7
A: 4^13
B:-4 *****
C: 13
D: 1

  1. 👍 0
  2. 👎 0
  3. 👁 150
asked by Alya
  1. I just need it to be checked please.

    1. 👍 0
    2. 👎 0
    posted by Alya
  2. #1 no
    #2 yes
    #3 no
    #4 no
    #5 yes

    looks like somebody needs more review and exercises.

    1. 👍 0
    2. 👎 0
    posted by Reiny
  3. #1. negative exponents mean reciprocals.
    -(5)^-1 = -(1/5) = -1/5
    #2. ok
    #3. again with the negative exponents...
    -1/p^-6 = -1 / (1/p^6) = -1*p^6 = -p^6
    You can think of negative exponents as switching a number between top and bottom of a fraction, and changing between plus and minus (the exponent only!)
    x^-6 = x^06/1 = 1/x^6
    1/y^2 = y^-2
    1/y^-2 = y^2

    #4. when multiplying numbers, add powers
    6^3 x 6^10 = 6^13
    It's just a shorthand way of writing 6*6*6 * 6*6*6*6*6*6*6*6*6*6 = 6^13
    what you did was
    (6^3)^10 = (6*6*6) ... 10 times = 6^30
    you multiply the exponents when raising a power to a power

    #5. correct
    Though I wonder whether it was an accident, given your mistakes above. Too bad you didn't show any work ...

    1. 👍 0
    2. 👎 0
    posted by oobleck

Respond to this Question

First Name

Your Response